QBD (QUALITY BY DESIGN) APPROACH: DEVELOPMENT AND VALIDATION OF AN RP-HPLC METHOD FOR ESTIMATING IMEGLIMIN HCL AND ITS KETONE IMPURITY - GIRI, POOJA T.; CHABUKSWAR, ANURUDDHA R.; JAGDALE, SWATI C.; CHINDHE, SANTOSH A. (International Journal of Applied Pharmaceutics, 2025)
Objective: Quality by Design (QbD) is a structured approach that ensures consistently high-quality outcomes by following a systematic methodology. This study aimed to develop and validate a robust and reliable Reverse-Phase High-Performance Liquid Chromatography (RP-HPLC) method for the simultaneous quantification of Imeglimin hydrochloride (IMG) and its ketone impurity, Imeglimin Ketone Impurity (IKI), utilizing a Quality by Design (QbD) approach to ensure enhanced method precision, accuracy, and regulatory compliance. Methods: A risk-based strategy guided method development, employing the Agilent Zorbax Bonus RP (AZB-RP) column (25 cm×4.6 mm, 5.0 µm) under isocratic elution with a Mobile Phase (MP) of Trifluoroacetic acid (TFA) and Acetonitrile (ACN) (45:55 v/v). Chromatographic conditions included a flow rate of 0.45 ml/min, an injection volume of 10 µl**, and a column temperature of 30 °C. A Central Composite Design (CCD) was applied to study the influence of MP ratio and Flow Rate (FR) on Critical Analytical Parameters (CAPs) using Design Expert 13.0 software. Results: The method showed excellent linearity with R² = 0.9998 for imeglimin hydrochloride (80–120 ppm) and R² = 0.9994 for its ketone impurity (4–6 ppm) at 238 nm. The recovery was 100.02–100.78% for imeglimin hydrochloride and 99.98–100.02% for the impurity. The Limit of Detection (LOD) and Limit of Quantitation (LOQ) for the impurity were 0.23 ppm and 0.70 ppm, respectively. The Analysis of Variance (ANOVA) results confirmed the model’s significance and predictive ability, highlighting the method’s robustness and reliability for routine quality control applications. Conclusion: The QbD-based RP-HPLC method described here is accurate, precise, and robust for the simultaneous estimation of IMG and IKI and can be used for routine quality control.